Adolescent nutrition in Indonesia: What have we learned? - Go, Ara; Olney, Deanna K. (International Food Policy Research Institute, 2020)
Investments in adolescent health have the potential to influence the future course of global health by improving the health and nutritional status of adolescents themselves, their life trajectories in adulthood, and the lives of their future children (1,2). Despite the growing recognition of the importance of adolescent health and nutrition (1–6), very few policies and programs have been designed and imple-mented to improve adolescent nutrition especially in low- and middle-income countries. There is also little evidence on how to effectively address the health and nutrition needs of adolescents from well-designed program effectiveness studies. Having a clear understanding of the nutritional problems of adolescents, and the drivers of those problems are prerequisites to developing appropriate policies and programs to improve adolescent nutrition, health and well-being. This brief offers a concise overview of the key nutritional challenges among Indonesian adolescents and current policies and programs to address these challenges. It also highlights other programs and policies to consider based on regional and international experiences.